Pengaruh Penggunaan Media Assembler Terhadap Motivasi dan Prestasi Belajar Siswa pada Materi Sistem Pernapasan - Mira Wahyuni; Dini Indah Syahfitri; Putri Rizq Ahyari; Rifqi Khoir Afdan; Syntia Zayrani (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
Media is a form of communication that aims to send messages from the sender to the recipient in oral or written form. According to Sriyanti, the types of media that are often used in learning include; print media, practical media, interactive media, E-Learning and M-Learning. The aim of the research carried out was to determine the effect of using assembler media on student motivation and learning achievement in respiratory material. This research used research and development methods. This is a research method used for a particular product and testing the effectiveness of the product. The increase in students' conceptual understanding reflects the positive influence of Assembler media on student learning achievement. Apart from that, the use of this media also has the potential to increase students' learning motivation, although direct evaluation of motivation was not carried out in this research. However, positive responses from students to such media can be considered as a potential indicator of increased motivation